"Каскад" на связь не вышел: роман / И. Срибный - Срибный Игорь (Спецназ. Офицеры, 2011)
Экземпляры: Б-Зетымский ФО-7 (20111027) / Инвентарный номер: 1 / Цена: 70.00 / Авт.знак: С 75 / ББК: 84(2Рос-Рус)6